Intraoperative methadone for postoperative pain in adult patients undergoing tonsillectomy—a randomised controlled trial - Michael Bøndergaard; Peter Gaarsdal Uhrbrand; Tutku Karaca; Marianne Rhode; Thomas Kjærgaard; Rene Thunberg Svendsen; Tejs Ehlers Klug; Lone Nikolajsen; Kristian Dahl Friesgaard (BJA Open)
Background: Tonsillectomy is a common procedure often associated with severe postoperative pain. This study hypothesised that methadone would provide superior postoperative pain relief and reduced opioid consumption compared with fentanyl. Methods: A total of 120 adult patients undergoing elective bilateral tonsillectomy were randomly allocated to receive either methadone (0.2 mg kg−1; n=62) or fentanyl (3 μg kg−1; n=58) after anaesthesia induction. Joint primary outcomes were pain intensity (numeric rating scale, 0–10) at swallowing upon postanaesthesia care unit (PACU) arrival and cumulative opioid consumption (oral morphine equivalents) over 5 postoperative days. Secondary outcomes included pain at swallowing, PACU and hospital stay duration, sedation at 4 h, patient satisfaction at days 1 and 7, postoperative nausea/vomiting (PONV) on days 1–3, and PACU adverse events. Results: Cumulative 5-day opioid consumption was lower in the methadone group (30 mg, inter-quartile range [IQR] 10–50 mg) vs the fentanyl group (49 mg, IQR 29–80 mg, P=0.002), driven by reduced use on day 1. Pain intensity was lower in the methadone group compared with the fentanyl group in the PACU (4, IQR 3–5 vs 5, IQR 4–7, P=0.0004), at 24 h (P=0.005) and 48 h (P=0.03). More patients in the methadone group experienced moderate to severe PONV at 24 h (45.0%, vs 14.1%, P=0.001), 48 h (43.3% vs 17.6%, P=0.005), and 72 h (33.9% vs 18.2%, P=0.03). Secondary outcomes, including patient satisfaction, sedation, and discharge times, did not differ significantly. Conclusion: Methadone reduced opioid consumption and pain intensity but increased PONV. Identifying risk factors for both severe postoperative pain and PONV may help guide patient selection for methadone use. Clinical trial registration: NCT05445856, EudraCT ID 2022-002496-11.